The Role of Electrochemotherapy in the Cutaneous and Subcutaneous Metastases From Breast Cancer: Analysis of Predictive Factors to Treatment From an Italian Cohort of Patients - Russano, Francesco; Del Fiore, Paolo; Di Prata, Claudia; Pasqual, Andrea; Marconato, Roberto; Campana, Luca Giovanni; Spina, Romina; Gianesini, Carlo Maria; Collodetto, Alessandra; Tropea, Saveria; Dall’Olmo, Luigi; Carraro, Sabrina; et al. (Frontiers in Oncology, 2021)
The treatment of cutaneous and subcutaneous localizations from breast cancer(BC)is still a therapeutic challenge. Electrochemotherapy (ECT) is one of the available options, and it is characterized by the association between the administration of a chemotherapic agent (Bleomycin) with the temporary raise of permeability of the cellular membrane induced by the local administration of electrical impulses (electroporation). ECT represents an effective therapy for loco-regional control of this disease. This study aimed to investigate the predictive factors of response in cutaneous and subcutaneous localizations from breast cancer treated with ECT. We decided to evaluate the response to this treatment in 55 patients who underwent ECT between January 2013 and March 2020 at our Institute. We performed a monocentric retrospective cohort study. ECT was administered following the ESOPE (European Standard Operative Procedure of Electrochemotherapy) guidelines, a set of criteria updated in 2018 by a panel of European experts on ECT who defined the indications for selecting the patients who can benefit from ECT treatment and the ones for technically performing the procedure. The responses were evaluated with the RECIST criteria (Response Evaluation Criteria in Solid Tumor). We found after 12 weeks of treatment a complete response (CR) in 64% of our patients. From the analysis divided for subgroups of covariates is emerged that lower BMI, reduced body surface and absence of previous radiation treatment could be predictive for a better complete response. This study suggests that the efficacy of the ECT treatment is related to the concurrent systemic therapies while administering ECT. The association between ECT and immunotherapy has offered better results than the association between ECT and chemotherapy (p-value = 0.0463). So, ECT is a valuable tool in the treatment of cutaneous and subcutaneous metastases from breast cancer and its efficacy in local control of these lesions improves when it is well planned in a therapeutic scenario.